Verification the performance of Microsoft SQL Server / Nageswary Gannapathy - Nageswary , Gannapathy (2002)
Microsoft SQL Server is a client / server based relational database management system (RDBMS) that uses T-SQL as its dialect of the SQL language. A client / server database is an application that is divided into a part that runs on a server and a part that runs on workstations (clients). The server side provides security, fault-tolerance, performance, concurrency, and reliable backups. The client side provides the user interface. SQL Server developers have the responsibility for designing and implementing the databases. Designing n good database start with understanding the client’s requirements for the database. SQL Server administrators have the responsibility for the day-to-day tasks of mai ntaining and managing the databases. SQL Server administration involves backing up databases and restoring them when necessary, setting up and managing users, managing database security, managing the replication environment, tuning the database system, and trouble shooting any problems that arise. In this proposal, the Verification the performance of Microsoft SQL Server 7.0 performance will be presented. The proposal mostly will touched on the part of tuning and indexes of SQL Server to perform an optimizer performance and shows how it works on retrieving columns and rows of the real datas. For this purpose, a system will be developed to communicate with SQLServer.